High spatiotemporal resolution optical measurements of two-stage ignition and combustion in Engine Combustion Network Spray D flames - Sim, Hyung Sub; Weiss, Lukas; Maes, Noud; Pickett, Lyle M. (Case studies in thermal engineering, 2024)
This study explores flame structures and combustion dynamics in high-pressure n-dodecane fuel sprays, focusing on the formation and consumption of formaldehyde (CH2O) during autoignition and the development of poly-aromatic hydrocarbons (PAH) as soot precursors. These processes are crucial for optimizing combustion efficiency and reducing emissions. However, traditional approaches, which rely on single-shot measurements or ensemble-averaged visualizations, often overlook critical early-stage processes during low-temperature ignition. To overcome these challenges, we employed an innovative high-speed planar laser-induced fluorescence (PLIF) technique at 50 kHz using a pulse-burst Nd:YAG laser system with an excitation wavelength of 355 nm. This approach, applied for the first time to Engine Combustion Network (ECN) Spray D flames, provides unprecedented insights into the combustion processes at varying ambient temperatures and oxygen concentrations. Additionally, simultaneous high-speed schlieren imaging at 100 kHz was used to visualize spray penetration, first-stage ignition, and thermal expansion zones. Our findings reveal that, similar to Spray A flames, CH2O forms in cold, fuel-rich zones well upstream of the combustion zone. However, in Spray D flames, the schlieren signal softening observed in the jet's head does not lead to complete disappearance, and the CH2O signal is absent from the full head of the spray. During the second-stage ignition, CH2O consumption accelerates due to high-temperature reactions, leading to a significant reduction in its signal. Unlike the mushroom-shaped structure seen in Spray A flames, Spray D flames exhibit a quasi-steady PAH phase structure, with lean peripheral mixtures insufficient for soot precursor formation. Notably, reducing ambient oxygen concentration to 13 % while maintaining or increasing temperature prolongs the presence of CH2O, highlighting its influence on ignition dynamics and oxidation processes in dodecane spray flames. This study provides new insights into the combustion mechanisms of high-pressure sprays and offers valuable data for developing next-generation combustion technologies, including models, aimed at improving efficiency and reducing emissions.